Reexamining Multisystem Desmoid Tumors Linked to Gardner’s Syndrome: A Clinical Case - Haijia Zhang; Yongjie Wu; Xiushan Dong; Jie An (Case Reports in Gastrointestinal Medicine)
A variation of familial adenomatous polyposis (FAP), known as Gardner’s syndrome (GS), can manifest as extraintestinal tumors, such as desmoid tumors (DTs). A key part in the diagnosing process is played by the clinician. Because DT frequently occurs before intestinal polyposis develops, doctors can identify the underlying illness early by looking for DT’s telltale signs. Nevertheless, in this instance, the patient’s failure to recognize the illness promptly following the excision of the tumor in the abdomen wall caused a delay in the diagnosis and impacted the disease’s course.